2015
DOI: 10.1002/anie.201502451
|View full text |Cite|
|
Sign up to set email alerts
|

Epitope Targeting of Tertiary Protein Structure Enables Target‐Guided Synthesis of a Potent In‐Cell Inhibitor of Botulinum Neurotoxin

Abstract: Botulinum neurotoxin (BoNT) serotype A is the most lethal known toxin and has an occluded structure which prevents direct inhibition of its active site before it enters the cytosol. We combine in situ click target-guided synthesis with synthetic epitope-targeting to exploit the tertiary structure of the BoNT protein as a landscape for assembling a competitive inhibitor. A substrate mimicking peptide macrocycle is used as a direct inhibitor of BoNT. An epitope targeted in situ click screen is utilized to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Previous efforts have demonstrated that binding affinity enhancement through cooperativity can be achieved by conjoining two binders against a target protein via a chemical linker . The length of the linker should correspond to the distance between the first and second epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous efforts have demonstrated that binding affinity enhancement through cooperativity can be achieved by conjoining two binders against a target protein via a chemical linker . The length of the linker should correspond to the distance between the first and second epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…The results here with mAbs confirm our earlier studies with a single domain antibody that mAbs that bind to the α-exosite, or other sites within the extended substrate-binding groove can inhibit substrate cleavage. Such exosites have been targeted for inhibitor development to other toxins [ 37 , 38 ] and more recently for BoNT/A [ 52 ], and a refinement to this approach could be to string together small molecules binding at different sites to achieve avidity and better substrate inhibition [ 53 ]. Alternatively, recently described liposomal “delivery vehicles” could be used to deliver inhibitory single chain or single domain antibodies into motor neurons to inhibit BoNT and reverse paralysis [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However done,t he general ability to target specific epitopes on specific proteins is enabling.F or example,t he broad flexibility of the epitope targeting strategy is already permitting exploitation of the tertiary structure of the drug target as as caffold for developing highly potent inhibitors. [10]…”
Section: Methodsmentioning
confidence: 99%
“…Akt1 E17K (Protein kinase Bwith oncogenic point mutation) [9] Biotin-PEG 5 -PEVAIVKEGWLKKRGK Y-Pra-KTWRPRYFLLKNDG yleaf (Li)6 1nm 54 nm XII. BoNT ALC(Botulinum neurotoxin serotype Alight chain) [10] Az4-SFGHEVLNLTRN-PEG 4 -Biotin (amino acids 166-179)…”
Section: Monoclonalantibodies(mabs)raisedagainstshortpeptidementioning
confidence: 99%